Red cell distribution width as a prognostic indicator in medical and surgical ICU patients - Vural, Aski; Cinar, Fadime; Bulbuloglu, Semra; Karamelek, Arife (Frontiers in Medicine, 2025)
BackgroundRed cell distribution width (RDW) has been investigated as a clinical predictor in different study populations. However, its prognostic usefulness in medical and surgical intensive care units remains unknown. This study investigates the role of RDW as a prognostic factor in this specific patient population.ObjectiveThis study examined the relationship between red cell distribution width and other blood parameters as a prognostic indicator among patients treated in medical and surgical ICU.MethodsThis study is observational in type and its sample consisted of n = 197 patients treated in the medical and surgical ICU (msICU) of a public hospital of Istanbul and during 2023. In this study, personal characteristics (age, gender etc.), clinical characteristics (comorbidity, presence of catheters, length of stay etc.) and clinical/laboratory blood parameters (the RDW coefficient of variation (CV), C reactive protein (CRP), albumin, platelet (PLT) etc.) of msICU patients were analyzed. The relationship between clinical/laboratory parameters was examined using the Pearson correlation test, and changes in RDW values according to patient characteristics were examined using ANOVA and independent sample t-tests.ResultsIn this study a positive, strong and statistically significant relationship existed between RDW and lactate (r = 0.704, p = 0.004) and CRP (r = 0.759, p = 0.026), and creatinine (r = 0.729, p = 0.001). It was reported that a negative, weak and statistically significant relationship existed between RDW and albumin (r = −0.172, p = 0.015) and PLT (p = −0.169, p = 0.011). The patient characteristics such as inotropic and vasopressor use, multiple comorbidities, APACHE II score, and surgical experience were factors that increased RDW levels (p < 0.05). Patients in the postoperative period and patients with pressure sores had higher RDW values and these differences were statistically significant (p < 0.05).ConclusionAs a result of this study, RDW level was associated with levels of lactate, CRP, albumin, platelet and creatinine among patients in the medical and surgical ICU. The patients with chronic wounds, comorbidities, and/or certain medications and in deceased patients, were associated with increased RDW. RDW may be a useful marker as a prognostic criterion to validate clinical status.